Leadership mastery in turbulent times - Herb Kindler (Thomson Course Technology, 2006)
Leadership Mastery in Turbulent Times is a powerful guide to the changing roles and new skills required to be an effective and ethical leader. Master these skills as you learn how to fuel creativity and productivity within an organization and how to energize performance. &a wonderful tapestry, almost poetic in its articulation.